2006
DOI: 10.2527/jas.2005-539
|View full text |Cite
|
Sign up to set email alerts
|

Secreted proteins and genes in fetal and neonatal pig adipose tissue and stromal-vascular cells1

Abstract: Although microarray and proteomic studies have indicated the expression of unique and unexpected genes and their products in human and rodent adipose tissue, similar studies of meat animal adipose tissue have not been reported. Thus, total RNA was isolated from stromal-vascular (S-V) cell cultures (n = 4; 2 arrays; 2 cultures/array) from 90-d (79% of gestation) fetuses and adipose tissue from 105-d (92% of gestation) fetuses (n = 2) and neonatal (5-d-old) pigs (n = 2). Duplicate adipose tissue microarrays (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 64 publications
5
47
0
1
Order By: Relevance
“…Analyses of the ASC and adipocyte proteome by mass spectrometry and other approaches have documented the identity of Ͼ200 proteins in both the undifferentiated and adipose differentiated cells. [73][74][75][76][77][78][79] The human ASC proteome shares features in common to that reported for fibroblasts, MSCs, and other lineages. 74 …”
Section: Immunophenotypementioning
confidence: 65%
“…Analyses of the ASC and adipocyte proteome by mass spectrometry and other approaches have documented the identity of Ͼ200 proteins in both the undifferentiated and adipose differentiated cells. [73][74][75][76][77][78][79] The human ASC proteome shares features in common to that reported for fibroblasts, MSCs, and other lineages. 74 …”
Section: Immunophenotypementioning
confidence: 65%
“…Nevertheless, the profile of the secretory products of ASCs has only recently begun to be characterized at the mass spectrometry level. Although there are a number of papers dedicated to ASCs proteomic characterization [43][44][45][46] , most of them are actually focused on the proteome of cell lysates rather than the characterization of the secretome itself. A recent study characterized the ASCs secretome in the context of differentiation towards the adipogenic lineage [47].…”
Section: Ascs Secretome -Basics and Possible Appli-cationsmentioning
confidence: 99%
“…Hausman et al [9] have previous reported that 5 -7 day old pig adipose tissue expresses a variety of adipokines. However, the present study is the first attempt to examine the relationship of growth rate and adipokine expression within adipose tissue in vivo during the preweaning period.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, adiponectin, lipoprotein lipase (LPL) and fatty acid synthase (FAS) were selected because they are markers for adipose differentiation in swine [16]. The interleukins 1β, 6 and 15 were included because they have been identified by Hausman et al [9] to be expressed by neonatal pig adipose tissue using proteomic analysis. Tumor necrosis factor α was examined as it has been the most characterized of all adipokines and has key regulatory roles in the expression of a variety of proteins, including the adipokines MIF and CCL2, which were included in this study.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%